Analysis of Trends and Challenges in the Implementation of PjBL-ESD at the Secondary Education Level: A Systematic Literature Review - Garmita Febriani Widaningsih; Prasetyorini Djarot; Indarini Dwi Pursitasari (Jurnal Ragam Pengabdian, 2026)
This systematic literature review investigates the trends and challenges of Project-Based Learning (PjBL) integrated with Education for Sustainable Development (ESD) at the Senior High School level from 2020 to 2025. Following PRISMA 2020 guidelines, the study synthesizes empirical data from Scopus, Web of Science, and Google Scholar through a four-stage process: identification, screening, eligibility, and inclusion. Results indicate a significant surge in PjBL-ESD studies since 2020, driven by the SDGs "Decade of Action" and curriculum reforms such as Indonesia's "Kurikulum Merdeka". The integration of digital scaffolding, including project-based e-modules and mobile learning, effectively mitigates cognitive load and enhances 21st-century skills, with critical thinking showing average N-gain scores ranging from 0.39 to 0.70. The inclusion of local wisdom and ethnoscience fosters cultural sustainability alongside ecological literacy. However, systemic barriers including teacher readiness, curriculum rigidity, and assessment misalignments remain significant hurdles. This review concludes that PjBL-ESD success requires structured digital ecosystems and policy-level support to bridge the gap between sustainability awareness and action competence.